PENGARUH PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA CLASSROOM BERBASIS ETNOMATEMATIKA KEPULAUAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MAHASISWA CALON GURU MATEMATIKA - Sisilia Marcelina Taihuttu; John Nandito Lekitoo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematical problem-solving ability is one of the essential competencies that prospective mathematics teachers must possess. However, this ability remains suboptimal because mathematics instruction tends to emphasize procedural knowledge rather than contextual problem solving. This study aimed to analyze the effect of Problem-Based Learning (PBL) assisted by GeoGebra Classroom based on island ethnomathematics on the mathematical problem-solving ability of prospective mathematics teachers in the topic of vectors. This study employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The participants consisted of 20 second-semester students of the Mathematics Education Study Program, PSDKU University of Pattimura, Southwest Maluku Regency, selected through total sampling. The research instrument was a mathematical problem-solving test developed based on Polya’s problem-solving indicators. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the paired-samples t-test. The results indicated that the mean score of students' mathematical problem-solving ability increased from 35.43 in the pretest to 77.61 in the posttest. The Shapiro–Wilk test showed that the difference scores were normally distributed (Sig. = 0.077 > 0.05). Furthermore, the paired-samples t-test revealed a significance value of 0.001 (p < 0.05), indicating a statistically significant improvement after the implementation of the learning model. Therefore, Problem-Based Learning assisted by GeoGebra Classroom based on island ethnomathematics significantly improved the mathematical problem-solving ability of prospective mathematics teachers.